2010
DOI: 10.1007/s11120-010-9544-x
|View full text |Cite
|
Sign up to set email alerts
|

Membrane proteome of the green sulfur bacterium Chlorobium tepidum (syn. Chlorobaculum tepidum) analyzed by gel-based and gel-free methods

Abstract: Chlorobium tepidum is a Gram-negative bacterium of the green sulfur phylum (Chlorobia). Chlorobia are obligate anaerobic photolithoautotrophs that are widely distributed in aquatic environments where anoxic layers containing reduced sulfur compounds are exposed to light. The envelope of C. tepidum is a complex organelle composed of the outer membrane, the periplasm-peptidoglycan layer, and the cytoplasmic membrane. In addition to the outer and plasma membranes, C. tepidum contains chlorosomes attached to the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…We have also demonstrated higher levels of protein overlap for gel-free analysis of biological replicates of other bacterial species ( M. haemolytica and P. multocida ) and believe that the lower overlap observed for Y. ruckeri is a species-specific phenomenon. Clearly, the use of these complementary approaches resulted in improved overall coverage of the outer membrane proteome and was consistent with previous work in other bacterial species [44,[61], [62], [63],83,84].…”
Section: Discussionsupporting
confidence: 87%
“…We have also demonstrated higher levels of protein overlap for gel-free analysis of biological replicates of other bacterial species ( M. haemolytica and P. multocida ) and believe that the lower overlap observed for Y. ruckeri is a species-specific phenomenon. Clearly, the use of these complementary approaches resulted in improved overall coverage of the outer membrane proteome and was consistent with previous work in other bacterial species [44,[61], [62], [63],83,84].…”
Section: Discussionsupporting
confidence: 87%
“…Similar results were also obtained from mixotrophic growth with pyruvate or acetate (data not shown). Moreover, SDH/fumarate reductase-like proteins encoded by CT2040 -2042, not CT2266 -2268, were also reported by recent proteomic studies (27).…”
Section: Labeled Bchls In the Mixotrophic Cultures Withmentioning
confidence: 63%
“…3A also indicates that the transcript level of aclAB is ϳ6 -10-fold higher than gltA. The CS protein has been previously reported by the proteomic analysis of C. tepidum (27,28), and the studies by Hosoya-Matsuda et al (28) suggested that CS is inactivated under conditions when ACL is activated. Consistent with their working hypothesis, the enzymatic activity of ACL, not that of CS, can be detected in cell extracts of autotrophic and mixotrophic growth cultures (Fig.…”
Section: Labeled Bchls In the Mixotrophic Cultures Withmentioning
confidence: 87%
“…Qualitative and quantitative mass spectrometry-based proteomics have become a routine tool to examine proteome remodelling in different cellular states [15]. The whole proteome of C. tepidum is extensively studied by gel-based and gel-free methods [16][17][18][19][20][21][22]. Some reports have employed sample separation by 2D-IEF/SDS-PAGE and 2D-BN/SDS-PAGE allowing the identification of about 625 different [16,17,20].…”
mentioning
confidence: 99%